On two genera of spiny Pudicinae (Nematoda: Trichostrongylina) parasites of the spiny rat Proechimys simonsi (Mammalia: Echimyidae) from Peru - Guerrero, Ricardo (Zootaxa, 2019)
A new species of trichostrongyloid nematode, Acanthostrongylus secundus is described. It differs from the other species of the genus in the structure of the caudal bursa. Squamasnema amazonica is redescribed correcting the synlophe structure and moving the genus from Heligmonellinae to Pudicinae. Both species were collected in Proechimys simonsi from Peru. [Zoobank URL: urn:lsid:zoobank.org:act:EEDBD925-8539-4F5D-A276-4F735464BA6F]